2017
DOI: 10.1515/raon-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brain edema formation defined by MRI after LINAC-based stereotactic radiosurgery

Abstract: BackgroundPeri-lesional edema is a serious and well-known complication of stereotactic radiosurgery (SRS). Here we evaluated edema risk after SRS and assessed its formation and resolution dynamics.Patients and methods107 patients underwent SRS for heterogeneous diagnoses: 34 (29%) with arteriovenous malformations, 38 (35%) with meningiomas, 16 (15%) with metastatic tumors, 16 (15%) with acoustic neuromas, 3 with (3%) cavernomas, and 2 (2%) each with anaplastic astrocytomas and anaplastic oligoastrocytomas. Ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Edema associated with SRS is well known. In a study conducted by Harat M et al [ 38 ] in a heterogeneous population of patients treated with SRS, edema was observed in 17% of cases. These authors found no association between the presence of edema and tumor size, dose escalation, or histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edema associated with SRS is well known. In a study conducted by Harat M et al [ 38 ] in a heterogeneous population of patients treated with SRS, edema was observed in 17% of cases. These authors found no association between the presence of edema and tumor size, dose escalation, or histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that edema increases during the first 6-9 months of SRS and begins to decrease after this period [ 38 ]. Not all cerebral edemas are symptomatic or require treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the follow-up of this study is rather short. As an indirect phenomenon, the volume of brain edema develops within 6 months and lasts for months or even years after SRS or WBRT [ 87 ]. A recently published meta-analysis summarizing the clinical and preclinical impact of conventional photon RT on BBB permeability revealed that there were increased permeabilities in all acute (< 1 month), early delayed (1–6 months), and late-delayed (> 6 months) follow-up categories [ 88 ].…”
Section: Mechanisms Of Synergy In Concurrent Srs + Ici In Treating Br...mentioning
confidence: 99%
“…Moreover, the translocation or secretion level of DAMPs seemed to correlate with the radiation dose positively [ 92 ]. However, excessively high doses can cause damage to surrounding healthy tissues and organs, for example, brain edema develops within 6 months and lasts for months or even years after SRS or WBRT [ 87 ]. Vanpouille ‘s study showed that Trex1 could be induced by radiation doses above 12–18 Gy, regardless of cancer type.…”
Section: Mechanisms Of Synergy In Concurrent Srs + Ici In Treating Br...mentioning
confidence: 99%
“…Currently available advanced radiotherapy techniques applying limited and fractionated doses have decreased the risk of symptomatic and debilitating brain oedema, as well as the need for treatment [31]. The risk of developing oedema is higher with stereotactic radiosurgery (SRS) than with fractionated radiation therapy [32,33]. Because vasogenic brain oedema can be challenging to detect on MRI, its prevalence is not well known.…”
Section: Oedemamentioning
confidence: 99%